(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Cluster randomization studies have become more common when traditional trials withindividual random assignment are impractical for theoretical, ethical, or practical reasons. While therehas been a lot of focus on developing methods for studying continuous or binary outcome data inclusters, the same cannot be said for ordinal data. Our empirical research is based on a database of s&p,moody’s, and fitch ratings for U.S.-based corporations from 2016 to 2021. Because it was at that timeframe that Fitch really started to make an impact in the American ratings industry, that’s where our focuswent. Credit rating sample size affects pairwise likelihood estimates: a multivariate approach Theaverage root-mean-square errors (RMSEs) of the coefficients and the thresholds parameters are almostsame across the several simulated data sets with different correlation structures.